Study of hydrate occupancy, morphology and microstructure evolution with hydrate dissociation in sediment matrices using X-ray micro-CT. (March 2020) - Wang, Daigang; Li, Yong; Liu, Changling; Zhan, Linsen; Lu, Hailong; Li, Chengfeng; Sun, Jianye; Meng, Qingguo; Liu, Lele
Abstract: Hydrate occupancy, morphology and spatial distribution in sediment pore can significantly affect the physical properties of hydrate-bearing sediment, but their evolutions with hydrate dissociation under various brine saturations are not well understood. X-ray micro-CT is employed to image the pore-scale dynamic process of methane hydrate dissociation in both sediments with different brine saturations. On the basis of processing and statistical analysis of X-ray CT images, several topological parameters, including volume, shape factor, fractal dimension and Euler characteristic of individual hydrate cluster, are selected to quantify hydrate occupancy, morphology and microstructure evolution with hydrate dissociation in the host sediments. Results show that the degree of brine saturation within the sediments can exert a significant impact on hydrate pore occupancy, morphology and microstructure connectedness during hydrate dissociation. In contrary to those of fully brine-saturated sediment, the topological parameters of individual hydrate cluster usually experience more dramatic changes with hydrate dissociation in partially brine-saturated sediment. It is inferred that in partially brine-saturated sediment the isolated hydrate clusters occupying in pore bodies are dissociated earlier in the initial experimental stage, and the dissociation of interpore hydrate frameworks interconnected through pore throats get dominated when hydrate saturation declines below a critical threshold value. On the other hand, in fully brine-saturated sediment the kinetics of pore-scale hydrate dissociation exhibit a completely opposite trend. Highlights: Hydrate occupancy, morphology and microstructure distribution hosted in host sediments are quantitatively evaluated. Their dynamic evolutions with hydrate dissociation in sediments under different brine saturations are well understood. Hydrate pore-scale dissociation kinetics in partially and fully brine-saturated sediments are specified.